REASONS CAUSING THE NEED FOR STRENGTHENING FUNDAMENTALS AND FOUNDATIONS DURING RECONSTRUCTION - Якименко, Олег (SWorldJournal, 2024)
The work considers the choice of the method of strengthening fundamentals and foundations, the organization and technology of the work; possible deterioration of working conditions and occurrence of deformations due to leaching, removal and liquefaction